SINDROMA NEFROTIK PADA PASIEN BERUSIA 20 TAHUN DENGAN HIVAN - Karina Nilasari (CHMK HEALTH JOURNAL, 2021)
Introduction: Kidney disease in patients with human immunodeficiency virus (HIV) infection has been ranked fourth in the cause of death after sepsis, pneumonia, and liver disease. HIV-associated nephropaty (HIVAN) is the most common. Case: The following is a case report, a male patient, 20 years old, presented with complaints of swelling all over his body, especially the legs and scrotum. The patient feels uncomfortable when breathing, less urine during the last 2 weeks. The patient had been diagnosed with HIV since 2 months ago. The patient took ARVs, but then stopped. There was an increase in urea and creatinine, proteinuria and hematuria on urinalysis as a sign of kidney problems. Renal biopsy showed segmental hyalinosis, focal, mild, intraglomerular neutrophil infiltrates, focal, mild and erythrocytes found in the tubular lumen. Conclusion: This occurred because it was preceded by damage of the glomerular podocytes due to viral infection, and continued with hyalinization and sclerosis. This condition causes the patient to experience nephrotic syndrome and hematuria. Keywords: human immunodeficiency virus, HIV-associated nephropaty, nephrotic syndrome